Reconstruction of Slowness Distribution of a Medium between Two Boreholes from First Arrival Traveltime Data - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2009)
We consider a problem of reconstruction of seismic wave speed distribution from a set of measured first arrival traveltimes in presence of strong velocity contrasts, which cause the problem to be highly non-linear. In this context, a stable iterative reconstruction algorithm, proposed by Berryman (1990) is studied. An attempt is therefore made to improve and also used it for a simple synthetic borehole test after writing its algorithm in a C++ code. The simulations results support the effectiveness of the method.
Keywords: Seismic tomography; Nonlinear Integral Equations; Inverse Problems; Nonlinear Programming and Convex Optimisation; ALGORITHM